MORALITAS HUKUM, LGBT DAN HAK ASASI MANUSIA DALAM PERSPEKTIF FIKIH SIYASAH - Enggar Wijayanto; Nuriah Hasibuan (Al-Usariyah: Jurnal Hukum Keluarga Islam, 2023)
The existence of LGBT groups in the Republic of Indonesia is still being debated quite fiercely. This is due to considerations of morality which consider the orientation and behavior of LGBT to deviate from the standard values ​​that already exist in society. The dialectic that arises is the standard of morality confronted with the principles of human rights and legal certainty. In the study of fiqh, especially siyasa fiqh, the issue of LGBT can be seen from the normative perspective of existing laws and regulations. Until now, there is no legality that allows LGBT to be legally recognized by law in Indonesia. This means that there is an aspect of legal vacuum in responding to the changing demands of the times that continue to grow. Therefore, the significance of this paper will be to explain how fiqh siyasa's review of answering the issue of LGBT legality is seen from a review of morality and human rights as aspects that cannot be separated from one another. The method used in this research is literature study, namely data obtained from library sources or secondary data, to be further analyzed using a predetermined theoretical framework. According to the latest research, LGBT existence in Indonesia is based on the opposite of morality, human rights, and conscience. It has to do with the Indonesian philosophy of pancasila, which has a religious, humanistic root, balances both individual and public interests, is not individualized liberals.